Case of sclerosing pneumocytoma combined with a typical carcinoid and pulmonary adenocarcinoma in different lobes. Issue 4 (5th May 2017) - Cho, Hwa Jin; Lee, Ji Hyeon; Lee, Geon Kook; Hong, Eun Kyung; Kim, Hyae Young
Abstract : We report the first case of a 62‐year‐old man with a sclerosing pneumocytoma (SP) combined with a typical carcinoid (TC) and pulmonary adenocarcinoma in different lung lobes. Computed tomography revealed two nodules. The radiological diagnosis was primary lung cancer and a metastatic nodule; however, no enlarged lymph nodes were observed. Histological and immunohistochemical analyses defined the 1.7 cm nodule in the right upper lobe as adenocarcinoma and the 1.3 cm nodule in the left lower lobe as SP combined with TC. This case is noteworthy because of the rarity of SP combined with TC, the comprehensive examination of frozen and permanent sections, and the clinical implications of the differential diagnosis of lung nodules.